Sosiale verantwoordelikheid as integrerende deel van openbare skakelwerk in die nywerheidsektor aan die oor-rand - Anna-Marie Roux; Sonja Verwey (Communicare)
Social responsibility has developed Into an Important Issue for companies and Industries A redefinition of the public relations practitioner's role with regard to the Interpretation of social change as well as to a broadening of the public relations practitioner's functions. A new organisational relationship between top management and the public relations practitioner needs to be established. The nature and scope of the public relations practitioner's involvement in the implementation of social responsibility programmes or actions. This study was to determine what the nature and frequency of social responsibility programmes amongst a group of East Rand industrialists is, as well as to determine to which extent the publicrelations practitioner plays an Integrating role in the design and implementation of social responsibility programmes and actions. However, most of these companies do not possess the necessary Infrastructure of a small or medium sized public relations department. The implementation of social responsibility programmes was therefore found not to be dependent upon the existence of the public rellations function. The authors conclude that social responsibility should be viewed as an integrated part of public relations practice at a strategic level and that it should be considered as a specialist function In which the public relations practitioner should specialise on a tertiary level.